Statin therapy and atherosclerosis regression - A. V. Susekov (Кардиоваскулярная терапия и профилактика, 1970)
Various clinical forms and complications of atherosclerosis remain the leading causes of morbidity and mortality in both developed and developing countries. HMG-CoA reductase inhibitors (statins) are the key components of pharmaceutical treatment in patients with dyslipidemia (DLP) and atherosclerosis. Statins have been thoroughly studied not only in randomised clinical trials with “hard” end-points, but also in the so called regression studies. The latter tested the hypothesis of qualitative and quantitative changes in coronary arteries (CA) due to aggressive reduction (-40-50% from baseline) of low-density lipoprotein (LDL) cholesterol levels. The results of the first regression studies justified the increase of statin doses in clinical practice, as well as led to large randomised clinical trials of statin therapy. In current regression studies, vascular atherosclerosis is monitored using such methods as intima-media thickness assessment, magnetic resonance imaging, and intravascular ultrasound. Reduced progression of carotid atherosclerosis (METEOR Study, rosuvastatin 40 mg/d; ENHANCE Study, ezetimibe 10 mg/d plus simvastatin 20 mg/d) and CA atherosclerosis (REVERSAL Study, atorvastatin 80 mg/d), as well as atherosclerosis regression (ASTEROID Study, rosuvastatin 40 mg/d), was demonstrated. Aggressive lipid-lowering effect (-40-50%), observed for high statin doses in modern regression clinical trials, was well-tolerated, with no severe adverse events. The results and principles of regression studies could be widely used in clinical practice, to optimise the treatment of severe DLP and atherosclerosis.